Depresión y su influencia en el rendimiento académico de un estudiante - Marrioth Laje, Celia Yanela (2020)
The present research study has been carried out in the Barreiro Educational Unit, the patient analyzed is a 12-year-old student, the central axis of analysis is the influence caused by depression in its academic performance. The objective is the analysis of the determining and intervening factors for the presence of depression in the observed patient. In the investigative process, certain techniques have been used to collect the relevant information and prepare an objective diagnosis, these are: clinical history, Beck depression inventory, human figure test and rain test. The main results indicate that the minor has a clinical picture of moderate depression, which is mainly caused by the negative situations she observes in her home, which in turn has significantly affected the other functional areas of her life. The investigation concludes by stating that the patient has symptoms of insecurity, sadness, loneliness and poor adaptability to the environment in which she is, in addition to low grades, which shows that depression directly influences academic performance.